INHIBITION OF THE GROWTH OF E. COLI AND CANDIDA BY SILVER COMPLEXE (I) WITH LIGANDS - Sadeq Jaafer Al-Tameemi (European Science Publishing, 2024)
This study is included synthesis and characterization of a number of complexes for Silver(I) ion, with molecular formula of the complexes: [{Ag(CAPR)(NO3). (H2O)} where: CAPR=Captopril. The complexe were prepared from silver nitrate with ligands 1:1 in 25 oC. The complexe were characterized by means of the the Ultraviolet visible spectrum UV, the flame atomic absorption, And the CHN analysis, This complexe were studied for their effect against some species of bacteria and fungi. The study showed that the complex {Ag(CAPR)NO3H2O} had the inhibitory ratio to bacteria and fungi.
Keywords: Silver Nitrate with Ligands, (FT-IR), UV, Bacteria and Fungi.